2023
DOI: 10.36348/sjef.2023.v07i03.001
|View full text |Cite
|
Sign up to set email alerts
|

Pension Assets Investments in the Nigerian Economy

Abstract: This study looked into pension assets investments and its impact in the Nigerian economy. The investments includes quarterly reports of corporate debt securities, government bond securities, mutual funds’ investments, money market instruments, private equity funds and real estate securities from 2004 – 2020, and was sourced from the statistics database of the National Pension Commission, the Central Bank of Nigeria and the World data bank. The statistical measures used to analyze the data are the descriptive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The study concluded that tax income has a favorable impact on the expansion of Nigeria's telecommunications industry. [26] studied how cash positioning affected mobile network providers' performance in Nigeria, particularly the increase in the number of active voice call subscribers. [27] used data from 2001-2017 and applied ARDL methodology to analyze the effect of mobile phones on economic growth in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded that tax income has a favorable impact on the expansion of Nigeria's telecommunications industry. [26] studied how cash positioning affected mobile network providers' performance in Nigeria, particularly the increase in the number of active voice call subscribers. [27] used data from 2001-2017 and applied ARDL methodology to analyze the effect of mobile phones on economic growth in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%